Former aux compétences du xxie siècle à l'aide du design - John Didier; Éric Tortochot (Université de Provence, 2021)
This article aims to highlight the transversal skills of the 21st century, while specifying their generic dimension for all training courses. Design education is positioned as a privileged crossroads in the teaching of the arts as well as in its interaction with other disciplines (science and technology). It actively participates in rethinking the role of education in the 21st century while encouraging, through its training challenges, the decompartmentalisation of disciplines. Initially, design is questioned at the epistemological level, in its positioning at the crossroads of science, technology, considered from the point of view of creative and technical activities, and the arts. Subsequently, design is studied as a discipline to train in conception, which involves four categories of generic skills, namely creativity, collaboration, communication and critical thinking. By way of perspective, we question the democratic issues targeted by education in the 21st century and dealt with by design in all training courses.